Erosive Potential of Various Beverages in the United Arab Emirates: pH Assessment - Mohannad Nassar; Md Sofiqul Islam; Noor Hasan; Ahmed Al-Khazraji; Husain Maki (Dubai Medical Journal, 2023)
Objectives: The United Arab Emirates (UAE) is one of the top 5 countries in the world in terms of juice consumption per capita. The rising consumption of beverages is a major contributor to a plethora of diseases, including heightened risks of developing obesity, diabetes, and osteoporosis. Beverages with low pH also tend to magnify the risk of long-term dental erosion. This paper evaluated the pH of various beverages in the UAE to help determine their erosive potential. Materials and Methods: 306 beverages were collected from different stores in the UAE. Drinks were categorized into 8 categories: carbonated drinks, energy drinks, sparkling water, iced teas, juices, malt beverages, coconut water, and sports drinks. Three readings were taken for each drink using a pH meter at room temperature. Results: 88% of all beverages had a pH of less than 4.0, and the remaining 12% had a pH of 4.0 or more. 37% of the beverages tested were extremely erosive (pH < 3.0), 51% were erosive (pH 3.0–3.99), and 12% were mildly erosive (pH ≥ 4.0). Bickford’s Classic Cola and Tesco Lemon Juice were the most acidic beverages (pH < 2.4). The most identified acids in the tested beverages were citric, phosphoric, ascorbic, and malic acids. Conclusions: The majority of beverages in the UAE are erosive to dentition as the pH is below 4. Future studies to raise public awareness on the effect of acidic drinks on tooth structure are needed.